Social Interaction Is Less Rewarding in Adult Female than in Male Mice - Anna E. Granza; Inês M. Amaral; Diogo G. Monteiro; Ahmad Salti; Alex Hofer; Rana El Rawas (Brain Sciences, 2023)
(1) Background: Positive social relationships are essential for mental and physical health. However, not all individuals experience social interaction as a rewarding activity. (2) Methods: Social interaction reward in mice can be assessed by social conditioned place preference (CPP). The aim of this study is to investigate sex-dependent differences in the neurological underpinnings underlying social versus non-social phenotypes, using adult male and female C57BL/6J mice. (3) Results: Adult female mice expressed significantly less social reward than males from the same strain. Accordingly, pairs of male mice spent more time interacting as compared to female pairs. Subsequently, we analyzed neuropeptides previously reported to be important regulators of social behavior such as oxytocin, vasopressin, and orexin, in addition to Ca2+/calmodulin-dependent protein kinase II (αCaMKII), shown to be involved in social reward. Levels of neuropeptides and αCaMKII were comparable between males and females in all investigated regions. Yet, a significant negative correlation was found between endogenous oxytocin expression and social reward in female pairs. (4) Conclusions: Sex differences in the prevalence of many mental health disorders might at least in part be due to sex differences in social reward. Therefore, more research is needed to unravel the candidate(s) underlying this behavioral difference.